The Influence Of Storytelling On 7th Grader Speaking Ability At SMP Negeri 22 Konawe Selatan - Dyah Setyorini, Wahyu; Sahlan, M.Pd, Dr. H.; Rahim, M.hum, Dr. Amiruddin (Journal of Language Education and Educational Technology (JLEET), 2016)
This research is accomplished to investigate how effective storytelling instructional for teaching English particularly speaking compared to the conventional tuition in EFL young learners. The researcher used quantitative data to investigate the effectiveness of using storytelling instruction take place in cohort B compared to the employment of conventional tuition in cohort A of the regular English course for the students of English Program in junior high school. Two research questions then were settled. The first question asked (1) do the students attending ‘the storytelling’ learning instruction perform better in their speaking proficiency than those attending conventional course? (2) What is the students’ motivation regarding the employment of storytelling instruction in of a speaking class?This study conducted at students’ English class on SMP Negeri 22 of Konawe Selatan who registered in academic year of 2013/2014. The total number of students involved in both of groups was 60 but the valid numbers were just 30 students in control group and 30 in experimental group as in taking sample, the researcher used Stratified Random Sampling. The instruments of data collection were speaking test and a questionnaire. The writing test collected by assigning pre-test to know students prior knowledge, treatment to conduct teaching speaking through storytelling instructional, and post-test to know students speaking achievement after giving treatment. The questionnaire was settled into 25 items of close-ended questionnaire and the data collection was conducted in post-test. The survey was made to investigate students’ motivation after given treatment under storytelling instructional compared to the conventional tuition. Findings through analysis of t-test in which  sig α < 0.05 or H0 is rejected and H1 is accepted both on treatment and control class, however after conducted independent t-test it was shown that there is a significant difference in terms of gain score between control and treatment class. Thus, it can be concluded that storytelling is effective compared to conventional tuition for teaching speaking. In addition, students had a very high motivation on the use of storytelling in learning speaking as the tested hypothesis shows a significant impact of students’ motivation and their improved speaking performance compared to these students who attended the conventional tuition. The finding suggests that integrating storytelling instructional into EFL young learners on speaking instruction is effective for enhancing students’ speaking performance and provides a positive learning experience